STUDY OF FLOUTING MAXIM FOUND IN SOME COSMOPOLITAN ADVERTISEMENT SLOGANS - AFSA, LAILIL JULIA (Jurnal Ilmiah Mahasiswa FIB, 2013)
Slogan that is used by manufacturer to attract the attention of customers usually flouts conversational maxim because it must be short and interesting. This phenomenon attracts the writer to analyze slogan in advertisement, especially cosmetics and body treatment slogans in Cosmopolitan magazine. In this study, the writer intends to identify the conversational maxims flouted in the advertisement slogans and to find out the meanings of the slogans based on Grice’s implicature theory. In order to answer the problems of study, the writer used descriptive qualitative approach and document analysis There are twelve slogans that are analyzed in this study. Only one slogan does not flout any maxim and the others flout at least one maxim. In other words, this advertisement does not briefs enough if the readers do not know the context, less informative, lack of evidence, and one of them is no direct relevance to the product. It happens due to the intention of making the slogan short. Consequently, producers sacrifice  information, relevance, clarity, and believability. Context is needed in analyzing the hidden meaning of the slogan. Without knowing the context of the slogan, the readers will have a difficulty in understanding the meaning of the slogan related to the product that is advertised. The hidden meaning of the slogan always brings the intention to promote the product and to persuade the customers to buy it. The writer suggests the next researcher who wants to conduct a similar research to understand the theory of pragmatics, especially flouting maxim and context. It is also expected that the further researchers use another theory to make their study more complete. In addition they can also use other objects, for example conversations in novels or scripts of films as the data. To know whether the hidden meaning of the slogan is understood easily or not, the further researchers can use a questionnaire or interview the customers.   Keywords: Conversational Maxim, Flouting Maxim, context, hidden meaning, slogans